UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA 1 MELALUI MODEL PEMBELAJARAN KONTEKSTUAL PADA MATERI PENDAPATAN NASIONAL DI MAN 2 PIDIE JAYA - Asnizar (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research was to know the increase of learning results about national income material by contextual learning model. This was classroom action research and conducted in three months, September to November 2021. It took place in XI Science 1 of MAN 2 Pidie Jaya. The subject of the research was twenty two students. The study was done in three cycles which each was by planning, acting, observing and reflecting. After the cycle 1 was conducted, it was found that nine of the students reached 75 up the MCC score and thirteen of them got 75 below the minimum score. It could be concluded that only 40.9% of them accomplished the material. In cycle 2, there was an increasing number of students accomplishing the material and reaching the minimum score. There were twelve or 54.5% of twenty two students. Last, in cycle 3, as many twenty or 90.9% of them were successfully completed the lesson based on the MCC score while the 9.1% remains did not get it.